Comparing Quasi-Parallel and Quasi-Perpendicular Configuration in the Terrestrial Magnetosheath: Multifractal Analysis - Gurchumelia, Alexandre; Sorriso-Valvo, Luca; Burgess, David; Yordanova, Emiliya; Elbakidze, Khatuna; Kharshiladze, Oleg; Kvaratskhelia, Diana (Frontiers in Physics, 2022)
The terrestrial magnetosheath is characterized by large-amplitude magnetic field fluctuations. In some regions, and depending on the bow-shock geometry, these can be observed on several scales, and show the typical signatures of magnetohydrodynamic turbulence. Using Cluster data, magnetic field spectra and flatness are observed in two intervals separated by a sharp transition from quasi-parallel to quasi-perpendicular magnetic field with respect to the bow-shock normal. The multifractal generalized dimensions Dq and the corresponding multifractal spectrum f(α) were estimated using a coarse-graining method. A p-model fit was used to obtain a single parameter to describe quantitatively the strength of multifractality and intermittency. Results show a clear transition and sharp differences in the intermittency properties for the two regions, with the quasi-parallel turbulence being more intermittent.